Detection of Medically Important Parasites in Fruits and Vegetables Collected from Local Markets in Dire Dawa, Eastern Ethiopia (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: medically important parasites; fruits and vegetables; local markets; dire dawa; ethiopia